Caracterização físico-química e capacidade antioxidante de borras de café oriundas de torras clara e escura e estudo do aproveitamento em muffins - Benincá, Daiane Bonizioli (2019)
Spent coffee grounds are the main by-product of the soluble coffee industry and domestic preparations, and this by-product may be of interest to the food industry because it has a significant amount of fiber and antioxidant properties due to the presence of phenolic compounds. In this context, the aim of this study was to evaluate the composition of coffee grounds obtained from light and dark roasted grains and to verify its applicability as a food ingredient in muffins. In the first stage of the study, the spent coffee grounds were obtained from arabica coffee beans, submitted to light and dark roasted and ground. The spent coffee grounds were dried in a tray dryer, initially at five temperatures (40, 50, 60, 70 and 80 °C) in three replicates. The drying kinetics and the model adjustment (Page, Lewis, Henderson & Pabis (H & P) and Midilli) were studied, and analyzes of moisture, total phenolic content and antioxidant activity (ABTS) were carried out on spent coffee grounds, and drying time were evaluated. The desirability function was used in the significant results, to define the drying conditions that maintained the most favorable characteristics of the spent coffee grounds. In the second stage of the study, the spent coffee grounds were dried at the temperatures defined previously and submitted to physicochemical, chromatographic and microbiological analyzes. Subsequently, the spent coffee grounds that had the best characteristics was chosen and it was applied in muffins, that were characterized by physical, physicochemical and chromatographic analyzes. The results showed that only moisture, drying time and energy expenditure were influenced by the drying temperature (p<0,05) in spent coffee grounds drying. For the desirability function, the best drying temperatures were obtained, from 56 °C for spent coffee grounds light roasted and 61 °C for spent coffee grounds of dark roasted. Caffeine, trigonelin, chlorogenic acid (5-CGA), hydroxymethylfurfural (HMF), total phenolic content, antioxidant activity (ABTS and DPPH), proteins, carbohydrates and ashes were significant (p<0.05) and the concentrations found were higher in the spent coffee grounds from light roast. Lipid concentration was higher in the spent coffee grounds of dark roasted. Microbiological analyzes demonstrated that both coffee grounds were suitable for later use. Due to the best characteristics, the spent ground coffee from light roast was chosen to be applied in muffins at the concentrations of 0, 1, 16, 31, 46 and 61% (in partial substitution to wheat flour) and the compromised acceptance thresholds were determined) and rejection (LR). The obtained LAC was 1,72% and the LR was 85,82% spent coffee grounds addition. Caffeine, trigonelin, 5-CGA and total phenolic content of the muffins, increased with addition of the spent coffee grounds. The antioxidant activity (DPPH) increased until the concentration of 16% of addition and then presented stability. While for ABTS there was stability between 16% and 46% concentration and a new increase when 61% of spent coffee grounds were added. The color showed significant differences in all studied parameters (L *, a *, b * and ?E), with a value of ?E from 46% of spent coffee grounds addition was higher than 7, while the texture was only significant in parameters of hardness and resilience. Therefore, the application of spent coffee grounds as a food ingredient in moderate concentrations and close to the LAC is feasible, since: (i) it enriches the product, (ii) some texture characteristics are not influenced and (iii) adding 1,72% of coffee grounds (LAC), the acceptance of the muffin stimulus did not differ from acceptance of the muffin control